2-Keto-L-Gulonic Acid Improved the Salt Stress Resistance of Non-heading Chinese Cabbage by Increasing L-Ascorbic Acid Accumulation - Gao, Mingfu; Sun, Hao; Shi, Meijun; Wu, Qiqi; Ji, Dongxu; Wang, Bing; Zhang, Lixin; Liu, Yang; Han, Litao; Ruan, Xicheng; Xu, Hui; Yang, Weichao (Frontiers in Plant Science, 2021)
Salt stress has long been a prominent problem that restricts crop growth and agricultural development. Increasing the L-ascorbic acid (ASA) content of crops is an effective way to alleviate this stress. 2-Keto-L-gulonic acid (2KGA) is a precursor organic acid used in the industrial L-ascorbic acid (ASA) production. Simultaneously, it is also one of the degradation products of plant ASA. However, studies on the effects of 2KGA on ASA metabolism and salt stress are scarce. This also reflects the limitations of the current research on plant ASA metabolism. In this study, we evaluated the potential of 2KGA to improve salt stress (100 mM·L-1 NaCl) tolerance of non-heading Chinese cabbage (Brassica campestris ssp. chinensis). The results showed that the leaf and root biomass were significantly improved by 2KGA application. The levels of metabolites and enzymes related to stress resistance were increased. On the contrary, the levels of H2O2 and malondialdehyde (MDA) were decreased, and the damage of cell membrane lipid peroxidation was alleviated. Positive correlations between photosynthetic pigments and organic solutes, ASA and photosynthetic pigments, and ASA and antioxidant enzymes, as well as negative correlations between antioxidant enzymes and H2O2/MDA, were observed. Moreover, the expression of L-gulono-1,4-lactone oxidase, GDP-mannose pyrophosphorylase, dehydroascorbate reductase-3, and ascorbate peroxidase was increased by 2KGA treatment. These results suggest that exogenous 2KGA can relieve the inhibition of salt stress on plant growth, and the promoted ASA synthesis may be a critical mechanism. Our findings have significant implications for the development of ASA industry and agriculture.